Environmental literacy profile of Muhammadiyah senior and vocational high school students in Malang Raya, East Java: What's interesting? - Husamah, H.; Rahardjanto, Abdulkadir; Lestari, Nurdiyah; Hadi, Samsun (Universitas Islam Negeri Sumatera Utara, 2024)
Senior and vocational high school students need to have strong environmental literacy (EL) to face environmental challenges and support the achievement of SDGs. High EL levels, supported by spiritual values, encourage students to make wise, environmentally friendly decisions and become agents of environmental conservation. Muhammadiyah schools play an important role in this regard through subjects that integrate religion and life. However, there has been no mapping of spirituality-based EL profiles among Muhammadiyah students in Malang Raya. This study aims to analyze the spirituality-based EL profile of Senior and Vocational High School Muhammadiyah students in Malang Raya. Using a cross-sectional survey approach, EL data from 584 students in grades X, XI, and XII in nine Muhammadiyah schools were collected and analyzed based on gender, class, and parental education. The results showed that there was no significant difference in EL between male and female students, as well as between classes. However, parental education, especially fathers and mothers who did not attend school, had a significant effect, although the effect was small to moderate. These findings suggest that life experience and parenting factors may influence students' EL, and that educational environment factors require further exploration to fully understand their influence.